Sufis and Saints' Bodies : Mysticism, Corporeality, and Sacred Power in Islam - Kugle, Scott Alan, 1969- (Book collections on Project MUSE., 2007)
Islam is often described as abstract, ascetic, and uniquely disengaged from the human body. The author of this book refutes this assertion in the first full study of Islamic mysticism as it relates to the human body. Examining Sufi conceptions of the body in religious writings from the late fifteenth through the nineteenth century, he demonstrates that literature from this era often treated saints' physical bodies as sites of sacred power. The book focuses on six important saints from Sufi communities in North Africa and South Asia.